Gambaran Tingkat Kecemasan Mahasiswa Keperawatan Saat Menghadapi Ujian Lisan Bahasa Inggris - Maryani Maryani; Sri Setyowati (STIKes Surya Global Yogyakarta, 2020)
Background of Study: A person who has a high anxiety, usually does not have a self-image. It often happens to students who will face oral examinations. Anxiety often arises when an oral exam takes place, so that it can reduce concentration in thinking during the exam.Objective: This research is aimed to determine the description of anxiety level on nursing students in speaking English test.Methods: This research is quantitative research by using cross sectional design method. The technique in collecting data used the Westside Test Anxiety Scale (WTAS). The data analysis technique used description analysis technique and univariat analysis.Results: The results indicated that the smallest anxiety level of 1.30 was included in anxiety comfortable/ not anxious, while the highest anxiety value of 4.90 was included in very high anxiety and an average value of 2.80. In addition, the level of anxiety with male sex as much as 3 respondents (2.0)%) who tend in highest anxiety, 1 respondent (0.7%) was not anxiety. While anxiety level with female gender tends to experience moderate anxiety as many as 42 respondents (28,%) the most dominant in other anxiety categories.Conclusion: The conclusion of this research was based on the level of anxiety with the moderate anxiety category was dominant in the face of the English oral examination. Whereas based on gender, the most dominant category was female sex with the highest, as many as 42 respondents (28.6%) who experience anxiety with a moderate category. Keywords : Anxiety, Nursing Students, Speaking English Test.